ANALISIS KESALAHAN TERJEMAHAN TEKS PANDUAN DARI BAHASA INDONESIA KE BAHASA INGGRIS - Neneng Sri Wahyuningsih (LINGUA : JURNAL ILMIAH, 2021)
The study aims at analyzing translation errors done by the 5th semester students at STBA LIA who were taking Indonesian-ENglish Translation Workshop. There are 28 participants in this study and the data are the translation of manual text which has been adapted and analyzed by using the 12 translation editing and revision by Mossop (2014). These parameters are normally used by editors in editing and revising translation work. The findings show that from that of 12 parameters, the mostly found parameters are mechanics with 46% occurrences, accuracy 13 %, sublanguage 11%, whereas the other parameters such as smoothness has 8.4% occurrences, layout 7.4%, idiom 7%, completeness 4%, and logic 3.2%. The conclusions show that the participants do not have problems at understanding the source text, but they do experience problems in the English’s, as the target language, grammar and natural language usage in English. In addition, they also have problems in choosing the right terminology, and also the usage of writing.